Silicone gels - comparison by derivation of material model parameters. (April 2017) - Previati, G.; Gobbi, M.; Mastinu, G.
Abstract: The mechanical properties of three different silicone gels were characterized by means of tension, shear and compression tests at large deformations. The non-linear behavior of the materials is taken into account and three material models (Neo-Hook, Yeoh, Ogden) for rubber-like materials have been considered in order to assess their capability to describe the behavior of the gels. The parameters of the material models are reported.